2019
DOI: 10.1080/21691401.2019.1606009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of hydrophobically modified fenugreek gum for potential hepatic drug delivery

Abstract: The objective of this study was to hydrophobically modify fenugreek gum (FG) and to further evaluate the potential application of the obtained derivative in liver-targeted drug delivery system. Stearic acid (C 18 ) was conjugated with FG (FG-C 18 ) by a simple esterification reaction. The obtained FG-C 18 was then characterized on its chemical structure by Fourier transform infrared spectroscopy and 1 H-nuclear magnetic resonance. The self-assembled nanomicelles (NMs) of FG-C 18 in water were prepared by an ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Moreover, many studies have demonstrated that galactosylated copolymers or grafted polysaccharides containing galactose residues on the surfaces of nanoparticles could enhance the drug level in the liver via the recognition of nanoparticles by ASGP-R [17,24]. The previous cellular uptake experiment [12] and the cytotoxicity assay performed in this study also indicated that GA/FG-C 18 NMs were first internalised into HepG2 cells, followed by GA release into the cytoplasm, which inhibited the growth of cells. The specific recognition between ligand and ASGP-R receptor was competed by the galactose solution.…”
Section: Pharmacokinetic and Tissue Distribution Studiessupporting
confidence: 51%
See 2 more Smart Citations
“…Moreover, many studies have demonstrated that galactosylated copolymers or grafted polysaccharides containing galactose residues on the surfaces of nanoparticles could enhance the drug level in the liver via the recognition of nanoparticles by ASGP-R [17,24]. The previous cellular uptake experiment [12] and the cytotoxicity assay performed in this study also indicated that GA/FG-C 18 NMs were first internalised into HepG2 cells, followed by GA release into the cytoplasm, which inhibited the growth of cells. The specific recognition between ligand and ASGP-R receptor was competed by the galactose solution.…”
Section: Pharmacokinetic and Tissue Distribution Studiessupporting
confidence: 51%
“…Preparation of glycyrrhetinic acid-loaded nanomicelles FG-C 18 was successfully synthesised and characterised according to its physicochemical properties in our previous report [12]. GA/FG-C 18 NMs were prepared by an ultrasonication dispersion method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the inner area of the particle is hydrophobic, the obtained systems may be useful in the delivery of active ingredients revealing low polarity [ 57 , 58 , 59 ]. In hydrophobic modifications, cholesterol [ 60 ], fatty acids [ 61 ] and other compounds [ 57 , 59 , 62 ] can be used. Parameters such as the particle diameter, the zeta potential and the loading efficiency can be modulated by adjusting the polymer chain length and the size of the hydrophobic residues [ 39 ].…”
Section: Micro- and Nanoparticle Fabrication Methodsmentioning
confidence: 99%
“…In one another modification, fenugreek gum was hydrophobically modified and stearic acid was conjugated with fenugreek gum by a simple esterification reaction. The results suggested that the resultant conjugate can be successfully employed for a liver‐targeted drug delivery (Zhou et al, 2019). Fenugreek gum can be chemically modified by cyanoethylation using acrylonitrile or oxidation (using sodium chlorite).…”
Section: Chemical Compositionmentioning
confidence: 99%